2020
DOI: 10.1186/s12877-020-01524-9
|View full text |Cite
|
Sign up to set email alerts
|

Adequate access to healthcare and added life expectancy among older adults in China

Abstract: Background: Adequate access to healthcare is associated with lower risks of mortality at older ages. However, it is largely unknown how many more years of life can be attributed to having adequate access to healthcare compared with having inadequate access to healthcare. Method: A nationwide longitudinal survey of 27,794 older adults aged 65+ in mainland China from 2002 to 2014 was used for analysis. Multivariate hazard models and life table techniques were used to estimate differences in life expectancy assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…Our findings are consistent with previous studies that have shown a mortality advantage among urban older adults relative to rural older adults in China [5,7,8,16]. With few exceptions, however, most of these studies did not distinguish urban-rural mortality differences by age or gender; and none of these studies explored the factors contributing to the differences in mortality by age or gender [5,7,16].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings are consistent with previous studies that have shown a mortality advantage among urban older adults relative to rural older adults in China [5,7,8,16]. With few exceptions, however, most of these studies did not distinguish urban-rural mortality differences by age or gender; and none of these studies explored the factors contributing to the differences in mortality by age or gender [5,7,16].…”
Section: Discussionsupporting
confidence: 90%
“…Historically, urban areas have had higher rates of infectious disease and mortality at the early stages of industrialization due to poor sanitation, hazardous working environments, and high population density-leading to a so-called urban mortality "penalty" [3]. However, today's urban areas usually have lower rates of mortality compared with rural areas due to improvements in infrastructure, better public health and medical systems, and overall advances in socioeconomic development [4][5][6][7]. These macro-level and institutional factors, along with a number of individual-level factors such as socioeconomic status [8], lifestyle and nutrition [9], and social networks [10], have been attributed to urban-rural disparity in mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Humans experience a relatively long, slow degradation of motor, sensory, and cognitive function and accumulate chronic diseases of aging such as sarcopenia, arthritis, hypertension, chronic kidney disease, diabetes, cardiovascular disease, and AD (Jaul & Barron, 2017). This is due in part to the aging of a population supported by good health care and nutrition (Chetty et al, 2016; Hao et al, 2020). However, with advancing age has come an increase in aging–related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Providing adequate healthcare services to individuals with most medical needs could contribute to more positive health outcomes. Hao et al [8] found that receiving adequate healthcare services was associated with longer life expectancy among Chinese older adults. Receiving adequate healthcare services could make a difference in healthy longevity among Chinese older adults as well [9].…”
Section: Introductionmentioning
confidence: 99%